2015
DOI: 10.1371/journal.pone.0127553
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Blood Transfusion on Exercise Capacity in Thalassemia Major Patients

Abstract: Anemia has an important role in exercise performance. However, the direct link between rapid changes of hemoglobin and exercise performance is still unknown.To find out more on this topic, we studied 18 beta-thalassemia major patients free of relevant cardiac dysfunction (age 33.5±7.2 years,males = 10). Patients performed a maximal cardiopulmolmonary exercise test (cycloergometer, personalized ramp protocol, breath-by-breath measurements of expired gases) before and the day after blood transfusion (500 cc of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…This indicates that the influence of exercise capacity before HSCT has the strongest effect compared with other factors. A relationship between hemoglobin values and exercise capacity was previously reported in healthy individuals [ 38 , 39 ] and patients with various pathological conditions [ 40 43 ], including those requiring HSCT [ 18 ]. Although the findings from these previous studies suggested that hemoglobin level influences fitness level, we showed that the hemoglobin level before HSCT did not influence post-HSCT fitness.…”
Section: Discussionmentioning
confidence: 97%
“…This indicates that the influence of exercise capacity before HSCT has the strongest effect compared with other factors. A relationship between hemoglobin values and exercise capacity was previously reported in healthy individuals [ 38 , 39 ] and patients with various pathological conditions [ 40 43 ], including those requiring HSCT [ 18 ]. Although the findings from these previous studies suggested that hemoglobin level influences fitness level, we showed that the hemoglobin level before HSCT did not influence post-HSCT fitness.…”
Section: Discussionmentioning
confidence: 97%
“…Production of red blood cells for transfusion can have several distinct benefits for healthcare and patient wellbeing ( Douay and Andreu, 2007 ; Goodnough and Murphy, 2014 ; Shah et al, 2014 ; Benedetto et al, 2015 ). Alloimmunization is one of the major complications of blood transfusion and particularly affects patients who are frequently transfused.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, anaemia is a relevant factor in determining the reduction of exercise capacity which is strictly related to blood haemoglobin content, but this factor does not explain entirely this limitation. Anaemia correction by blood transfusions in β-thalassemia patients is associated to a relevant increase of exercise performance, as demonstrated by Benedetto et al 2015 [23] that found an increase of 82.5 mL/min in V'O 2 peak for each g/dL of haemoglobin increase.…”
Section: Discussionmentioning
confidence: 88%